2017
DOI: 10.1186/s12885-017-3771-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the outcomes of HIV-infected persons receiving treatment for Kaposi sarcoma in Conakry-Guinea

Abstract: BackgroundMédecins Sans Frontières is supporting comprehensive HIV care and treatment for Kaposi Sarcoma (KS) in Guinea, where antiretroviral coverage is low and access to KS treatment is very limited. We aimed to evaluate treatment response and survival outcomes of epidemic KS in this setting.MethodsRetrospective survival analysis of routinely collected clinical data of HIV-infected patients with clinically diagnosed KS, receiving ART and chemotherapy consisting of a combination of bleomycin and vincristine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…A particular strength of our study comes from linking severity of disease at time of diagnosis with subsequent treatment course in a real-world setting. Similar to other resource poor settings, most patients in this Kenyan setting were diagnosed with KS when their disease was already at advanced stage, and not all patients had histologically confirmed disease [8,25,31,32]. We found that patients who were on ART for > 60 days prior to KS diagnosis were diagnosed at less advanced KS disease stage, which could either be due to the effects of ART itself (though we do not know who was virally suppressed), or due to the more frequent contact these patients had with the health system.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…A particular strength of our study comes from linking severity of disease at time of diagnosis with subsequent treatment course in a real-world setting. Similar to other resource poor settings, most patients in this Kenyan setting were diagnosed with KS when their disease was already at advanced stage, and not all patients had histologically confirmed disease [8,25,31,32]. We found that patients who were on ART for > 60 days prior to KS diagnosis were diagnosed at less advanced KS disease stage, which could either be due to the effects of ART itself (though we do not know who was virally suppressed), or due to the more frequent contact these patients had with the health system.…”
Section: Discussionmentioning
confidence: 74%
“…Prior studies on KS treatment with chemotherapy in sub-Saharan Africa have focused on outcomes of particular chemotherapy regimens, [17,18,[25][26][27] neither evaluated real-world delays in chemotherapy initiation, nor, perhaps most importantly, chemotherapy non-initiation in patients with chemotherapy indications. We know that there is often a significant delay between symptom recognition and successful initiation of cancer care in Africa [28].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to prior studies in sub-Saharan Africa reporting that 69 to 89% of KS patients present with T1 disease. 4,5,7,21,22 This finding contrasts with high income countries where there is much less T1 disease, with recent estimates of 34-35%. 14,23 Compared to prior studies, our documentation of advanced stage of disease is likely more representative and proximal in a multi-site sub-Saharan African setting.…”
Section: Discussionmentioning
confidence: 89%
“…However, the question remains which signs or symptoms of KS are predictive of KS mortality. In addition to TIS staging predictors, previous studies from both high and low income settings have found that pulmonary involvement, 11 woody edema, 22 low BMI, 26 low hemoglobin, 26 low albumin, 25 older age, 23 decreased performance status, 23,25 and positive HHV-8 DNA to be predictive of mortality. 6,27 The linkage of staging criteria with outcomes has recently been performed in the pediatric KS literature in Malawi, but has not yet been performed for the adult KS population in sub-Saharan Africa during the treat-all era.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the incidence of KS in sub-Saharan Africa and its hallmark presentation on the skin and visible mucous membranes (i.e., in areas where it theoretically can be detected in an early stage), more than 80% of all KS in sub-Saharan Africa is classified as late-stage at the time of diagnosis (2)(3)(4). Like many cancers, KS diagnosed in advanced stages has worse survival than early diagnosis (4,5). Probably more than most cancers, however, detecting KS early in sub-Saharan Africa could likely largely control the condition.…”
Section: Introductionmentioning
confidence: 99%